The determinants and the impact of bank regulations and supervision on the efficiency of Islamic banks - Nor Halida Haziaton binti Mohd Noor (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
This study sheds light the analysis of bank efficiency of 108 Islamic banks operating in 26 countries across MENA, ASIA and other regions from year 2004 to 2010. The two-stage approach is employed for this study. In the first stage, the non-parametric Data Envelopment Analysis (DEA) method is used to measure the technical efficiency scores of the Islamic banks. The second stage analysis is Multivariate Regression analysis where the unbalanced panel data regression model is employed to regress the efficiency scores on bank-specific, macroeconomics and bank regulations and supervision factors which could influence the efficiency levels of the Islamic banks. The empirical findings from the first stage bring forth the high degree of inefficiency of Islamic banks and suggest that the Islamic banking sector has been relatively managerially efficient in controlling their operating costs but have been operating at a relatively non-optimal scale of operations. In the second stage analysis, the findings have a very significant implications for the management of Islamic banks which helping the bank managers to apply strategies to raise the efficiency because the efficiency measures lead to knowledge about any disadvantages of the operation within the banks. The empirical findings from the second stage also has provide evidence on the impact of regulations and supervision on Islamic banks' efficiency where the findings suggest that in Asia and high-income countries, the stricter the supervisory power, the tighter the restrictions on non-banking activities and the stricter the private monitoring could enhance the level of efficiency of Islamic banks. Meanwhile, in MENA and middle-income countries, the stricter the capital requirement could decrease the level of efficiency of Islamic banks. The findings highlight the challenges and issues pertaining the existing regulations and the implications of Basel II framework towards the efficiency of Islamic banks and its importance in formulating the appropriate strategies in the aspects of policies of Islamic banking regulations and supervision